Intestinal Helminth Infections among Children with Disabilities in Bantul Regency, Special Region of Yogyakarta - Lala Foresta Valentine Gunasari; Elsa Herdiana Murhandarwati (Prodi Kesehatan Masyarakat FKM UIN Sumatera Utara Medan, 2021)
Due to physical, intellectual, mental, and/or sensory limitations, person with disabilities tend to experience obstacles and limitations in their ability to care for themselves, knowledge of health, and access to health services. As a result, people with disabilities are more at risk of experiencing health problems, one of which is intestinal helminth infection. The aim of this study was to assess the prevalence of intestinal helminth infections and associated risk factors among children with disabilities at school age in Bantul Regency, Special Region of Yogyakarta. A school-based cross-sectional study design was conducted from October until December 2019. A total of 130 stool samples were collected and examined by the flotation, Kato-Katz, Harada-Mori, and Baermann methods to detect the presence of helminth eggs and/or larvae. An interview with parents/guardians of the subject based on a questionnaire was conducted to obtain information regarding the associated risk factor. The overall prevalence of intestinal helminth infections among subjects was 1.5% (CI=95%). Of these, 0,07% (1/130) was positive for hookworm infection, and the remaining 0,07% (1/130) was positive for Trichuris trichiura. Analysis for all risk factors showed no statistically significant association between all risk factors and the intestinal helminths infections in the study subjects (p>0.05).